2023
DOI: 10.3390/microorganisms11010213
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility and Virulence of Enterobacteriaceae Isolated from Urinary Tract Infections in Benin

Abstract: Enterobacteriaceae represent one of the main families of Gram-negative bacilli responsible for serious urinary tract infections (UTIs). The present study aimed to define the resistance profile and the virulence of Enterobacteriaceae strains isolated in urinary tract infections in Benin. A total of 390 urine samples were collected from patients with UTIs, and Enterobacteriaceae strains were isolated according to standard microbiology methods. The API 20E gallery was used for biochemical identification. All the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 63 publications
(68 reference statements)
1
11
0
Order By: Relevance
“…Resistance profile to cephalosporins was impacted with high rates for TGC. E. coli strains showed high rates for TGC, as reported in Benin with 100% resistance of E. coli strains to cefixime and ceftriaxone (Assouma et al, 2023). However, the resistance rate to TCF was about 12.6% for E. coli, K. pneumoniae, and P. mirabilis UTI in Northern California (USA) (Mark et al, 2021) and 18.4% for E. coli, 30.7% for Klebsiella spp.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Resistance profile to cephalosporins was impacted with high rates for TGC. E. coli strains showed high rates for TGC, as reported in Benin with 100% resistance of E. coli strains to cefixime and ceftriaxone (Assouma et al, 2023). However, the resistance rate to TCF was about 12.6% for E. coli, K. pneumoniae, and P. mirabilis UTI in Northern California (USA) (Mark et al, 2021) and 18.4% for E. coli, 30.7% for Klebsiella spp.…”
Section: Discussionmentioning
confidence: 79%
“…However, in a study on the confirmation of the carbapenem profile of Enterobacterales, only 8.9% were confirmed resistant (Steward et al, 2003). Another study conducted in Benin reported resistance rates ranging from 12.5 to 66.6% of Enterobacterales to imipenem (Assouma et al, 2023). This low resistance rate to carbapenems could make these antibiotics an option for managing multidrug-resistant bacteria in our context and Ceftazidime-avibactam could be used to manage UTI caused by carbapenemase producing Enterobacteral such as KPC and OXA-48 producers (García-Castillo et al, 2018).…”
Section: Discussionmentioning
confidence: 98%
“…Another 2023 study which evaluated 390 urine samples from 2021-2022 isolated 103 Enterobacteriaceae (E. coli, Serratia spp., Klebsiella spp., Citrobacter freundii and Enterobacter intermedius). Although a low imipenem resistance rate was observed in 27.18% strains, no data on CP rates are available [48].…”
Section: Resultsmentioning
confidence: 99%
“…Adhesion proteins help A. baumannii and P. aeruginosa cells attach to surfaces and initiate biofilm formation, which includes fimbriae and type IV pili. Moreover, studies have shown the role of curli fimbriae genes ( csgA and csgD ) in the biofilm formation of Enterobacter isolates . A number of virulence-associated genes have been identified that play a key role in virulence and biofilm formation, including fimA (type 1 fimbriae gene), fyuA, and p pili genes ( papC and papD ) . Bacterial cell attachment with fimbriae, pili, and adhesin molecules is a crucial phase in the development of infections and biofilm formation that helps to avoid host immune responses.…”
Section: Biofilms: Fundamental Perspectivementioning
confidence: 99%